2015
DOI: 10.1111/all.12577
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of chronic rhinosinusitis: results from a cross‐sectional survey in seven Chinese cities

Abstract: BackgroundChronic sinusitis (CRS) is a common otorhinolaryngologic disease that is frequently encountered in everyday practice, but there is a lack of precise data regarding the prevalence of CRS in developing countries. We performed a national investigation in China to determine the prevalence and associated factors of CRS.MethodsWe conducted a cross-sectional investigation in 2012. A stratified four-stage sampling method was used to select participants randomly from seven cities in mainland China. All partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
316
3
22

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 367 publications
(355 citation statements)
references
References 37 publications
14
316
3
22
Order By: Relevance
“…(15) which was consistent with some studies discovering positive associations between sinus disease or CRS and asthma. (18,19) This conform our finding 61.6% of infected respondents suffer from sensitivity.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…(15) which was consistent with some studies discovering positive associations between sinus disease or CRS and asthma. (18,19) This conform our finding 61.6% of infected respondents suffer from sensitivity.…”
supporting
confidence: 92%
“…(14) but this finding unlike results of study in china which reported that The prevalence chronic rhinosinusitis among males was higher than that among females in the general population. (15) More than half 55.6% of infected respondents were between (21-30) years old. this finding conform with Kim et al whose found that A relatively higher prevalence was seen in those aged 15-34.…”
Section: Discussion:-mentioning
confidence: 99%
See 1 more Smart Citation
“…The bacterial taxa presented here are a few of the commensal and pathogenic species that have been implicated in CRS disease progression. This figure is adapted from the information in the following references 5,6,[8][9][10][11][12][13][14][15][16] .…”
Section: Balance Of Bacterial Taxamentioning
confidence: 99%
“…CRS is a condition which can be classified according to various symptoms of sinus inflammation with the time period at least two months or longer [1]. There are numerous factors can potentially induce rhinosinusitis including infection, allergy, inflammation or obstruction of the sinuses [1].…”
Section: Introductionmentioning
confidence: 99%